2017
DOI: 10.22146/ipas.12840
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Induced Resistance of Fusarium Wilt Disease (Fusarium oxysporum f.sp. cepae) by Salicylic Acid in Shallot CV ‘Bima Brebes’

Abstract: Fusarium wilt caused by Fusarium oxysporum f.sp.cepae (Foc) is one of the most important diseases of onion in Indonesia. Induced resistance was one of the effective techniques to acquire resistance to fusarium wilt in shallot. Salicylic acid (SA) had been inferred to be in endogenous signal in the systemic acquired resistance response of plants. This research aimed to study the effect of exogenously added SA to resistance in shallot callus cv. 'Bima Brebes' to fusarium wilt disease in vitro; and to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In this study, salicylic acid treatment had no significant effects on the incidence of Fusarium in shallots. A similar result was also reported by Khotimah et al (2017) that exogenous treatment of salicylic acid had no significant effects on the incubation period and the incidence of disease. Disease incidence is more influenced by the genetic structure of plant cultivar than the addition of exogenous salicylic acid.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, salicylic acid treatment had no significant effects on the incidence of Fusarium in shallots. A similar result was also reported by Khotimah et al (2017) that exogenous treatment of salicylic acid had no significant effects on the incubation period and the incidence of disease. Disease incidence is more influenced by the genetic structure of plant cultivar than the addition of exogenous salicylic acid.…”
Section: Resultssupporting
confidence: 89%
“…The first factor included TSS cultivars (Tuktuk, Sanren and Lokananta) and the second comprised the application method of salicylic acid (without salicylic acid and inoculation, without salicylic acid with inoculation, immersion treatment of salicylic acid with inoculation, spray treatment with inoculation as well as immersion and spray treatment with inoculation). The treatment of salicylic acid using immersion treatment was carried out by immersing TSS in a 15 ppm salicylic acid solution for 30 minutes following Khotimah et al (2017). The spray treatment was performed by spraying 15 ppm salicylic acid solution on the seedlings from the seeds as much as 50 ml per 500 cm 2 two days before planting (38 days after seedling) (Krishardianto and Sukma, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Although the mechanism by which SA stimulates root development is still unknown, it is possible that SA promotes cell division of root meristems, generating an increase in the size of the root cap and promoting the formation of lateral and adventitious roots. Khotimah et al (2017) have reported a "hormetic" in vitro response to SA. In V. planifolia, this effect was observed when the plantlet was applied with a dose of 7.5 µmol SA.…”
Section: In Vitro Effect Of Salicylic Acidmentioning
confidence: 99%